2017
DOI: 10.4081/ejtm.2017.7086
|View full text |Cite
|
Sign up to set email alerts
|

The road to Cybathlon 2016 - Functional electrical stimulation cycling Team IRPT/SPZ

Abstract: Functional electrical stimulation (FES) provides a good possibility to activate paralysed muscles and it has been shown to elicit substantial physiological and health benefits. For successful application of FES, a perfect symbiosis of the bike and the pilot has to be achieved. The road to the Cybathlon 2016 describes the different pieces needed for FES cycling in spinal cord injury. The systematic optimisation of the stimulation parameters and the Cybatrike, and sophisticated training contributed to the team’s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 15 publications
1
15
0
Order By: Relevance
“…Future studies should investigate long-term training protocols and compare SDSS and SES in SCI participants with well-trained muscles. Laubacher et al [79] reported a single case which compared SDSS and SES in a well-trained person with SCI in the context of preparations for the FES bike race at Cybathlon 2016 in Zurich [80]. In this case, P m e a n L , R with SDSS was more than twice as high as P m e a n L , R with SES.…”
Section: Discussionmentioning
confidence: 99%
“…Future studies should investigate long-term training protocols and compare SDSS and SES in SCI participants with well-trained muscles. Laubacher et al [79] reported a single case which compared SDSS and SES in a well-trained person with SCI in the context of preparations for the FES bike race at Cybathlon 2016 in Zurich [80]. In this case, P m e a n L , R with SDSS was more than twice as high as P m e a n L , R with SES.…”
Section: Discussionmentioning
confidence: 99%
“… 6 To involve the lower limbs during exercise among those with SCI, researchers often use functional electrical stimulation (FES) as a therapeutic exercise tool. 7 FES is applied over the skin surface of the muscles of the affected limbs in order to artificially activate paralyzed muscles 8 and produce functional movement. 9 FES can enable those with SCI to perform different functional tasks such as grasping, 10 walking, 10 standing, 11 transferring, 7 cycling, 12 and rowing.…”
Section: Introductionmentioning
confidence: 99%
“…One potential way to acutely improve electricallyinduced exercise is to reduce the overlap of activated fibers among stimulating electrodes. Current systems stimulate through multiple surface electrode pads [19][20][21][22] or implanted neural electrode contacts [23] at once and at high pulse amplitudes (PA) and/or pulse widths (PW) to engage as many muscle fibers as possible, particularly during knee extension phases of cycling. Though this can result in high initial power production, the large voltage fields produced by each electrode can overlap and limit performance as the exercise goes on.…”
mentioning
confidence: 99%